Fenomena Pernikahan Usia Dini Terhadap Ibu Pelaku Kekerasan Pada Anak Di Desa Rengasjajar, Kecamatan Cigudeg, Bogor - Chazizah Gusnita; Winna Faradilla Nulhakim (Deviance Jurnal kriminologi, 2017)
This qualitative research aims to analyze the factors causing the violence that is done by mother to child. This research was conducted in Rengasjajar village area, Cigudeg sub-district, Bogor. Early marriage has been a matter of great concern to this day. Factors that are usually the reason for early marriage include economic factors, educational factors, and stigma factors. Early marriage is very risky both in physical and mental health. In this study, researchers used Structural Victorian Theory and Social Conversion Theory. Early marriage causes unpreparedness to be a mother at a young age resulting in foster parenting errors by using violence. Violence includes verbal violence to physical violence. The results of this research is the stigma that makes teenagers afraid to not believe that says that women are not married at the age of 18 years old then it will be considered as an old maiden and it greatly affect the mindset of teenagers and make them to do early age marriage, people parents feel that violence in educating children may be done because parents have a right to it, control in the household is necessary because the control as a foundation to know the limits of not doing irregularities in this case violence to children both physical violence and verbal violence